PEMANFAATAN POJOK BACA UNTUK MENINGKATKAN MINAT BACA SISWA DI MADRASAH ALIYAH NEGERI 1 BANYUASIN - Alya Putri Salsabila; Rani Kurnia Vlora (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM Azramedia Indonesia, 2023)
This research is entitled Utilisation of Reading Corner to Increase Students' Interest in Reading at Madrasah Aliyah Negeri 1 Banyuasin. This study aims to understand how the use of the reading corner can increase students' interest in reading at Madrasah Aliyah Negeri 1 Banyuasin, as well as to identify the supporting and inhibiting factors in the utilisation of the reading corner to increase students' interest in reading at Madrasah Aliyah Negeri 1 Banyuasin. The research method is descriptive qualitative research conducted in the field, focusing on the research location. Data collection techniques were conducted through observation and interviews. The main data sources are the Head of Library and students at Madrasah Aliyah Negeri 1 Banyuasin. The results showed that the utilisation of the reading corner at Madrasah Aliyah Negeri 1 Banyuasin has successfully encouraged students' interest in reading which involves several strategies, such as educating students about the importance of reading, as well as encouraging them to read at the reading corner when facing difficulties in learning. In addition, the study also found that the reading corner is used as a reference and discussion place during learning, as well as a means of filling students' spare time